1993
DOI: 10.1084/jem.178.2.749
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of arthritis by an inhibitor of nitric oxide synthase.

Abstract: SummaryNitric oxide (NO), a toxic radical gas produced during the metabolism of I.-arginine by NO synthase (NOS), has been implicated as a mediator of immune and inflammatory responses. A single injection of streptococcal cell wall fragments (SCW) induces the accumulation of inflammatory cells within the synovial tissue and a cell-mediated immune response that leads to destructive lesions. We show here that NO production is elevated in the inflamed joints of SCW-treated rats. Administration of NG-monomethyl-t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
279
2
9

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 597 publications
(301 citation statements)
references
References 26 publications
11
279
2
9
Order By: Relevance
“…NO? has been implicated as a mediator of in¯ammatory arthritis in a model using injected streptococcal cell wall fragments (McCartney-Francis et al, 1993). LPS is synergistic with muramyl dipeptide, a synthetic peptidoglycan monomer analogue, in the inhibition of proteoglycan synthesis in chondrocytes (Ikebe et al, 1993), an effect which may be mediated by NO?…”
Section: Discussionmentioning
confidence: 99%
“…NO? has been implicated as a mediator of in¯ammatory arthritis in a model using injected streptococcal cell wall fragments (McCartney-Francis et al, 1993). LPS is synergistic with muramyl dipeptide, a synthetic peptidoglycan monomer analogue, in the inhibition of proteoglycan synthesis in chondrocytes (Ikebe et al, 1993), an effect which may be mediated by NO?…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reduced the severity of AIA (28,32,33) and of streptococcal cell wall-induced arthritis (26) in rats using N-methyl-L-arginine, a NOS inhibitor, which suggests a fundamental role for NO pathways in these experimental models (26,28). However, a recent evaluation of several iNOS inhibitors in AIA showed that aminoguanidine was able to suppress the level of urinary nitrate excretion during AIA without a reduction in arthritis severity (32).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibitors of NOS have been shown to suppress arthritis in several animal models (26,28,32,33,35), and increased levels of NO have been found in patients with rheumatoid arthritis (36,37). However, it has not been shown that NO is a requisite component of joint inflammation regardless of the cause of arthritis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This form of NOS is Ca¥ independent and, once expressed, produces large amounts of NO which may contribute to the host defence mechanisms and immunoregulation (Grabowski et al 1996(Grabowski et al , 1997Moncada et al 1997). It has been shown that in experimental arthritis induced by a single injection of streptococcal cell wall fragments in rats (McCartney-Francis et al 1993) the expression of inducible nitric oxide synthase (iNOS) gene was increased, and administration of l-NMMA profoundly reduced the joint swelling and distortion of the cartilage. It has been also shown that the levels of 3-nitro-tyrosine, which can be produced by NO-dependent oxidative damage, are elevated in the blood serum and synovial fluid in patients with rheumatoid arthritis (Kaur & Halliwell, 1994).…”
mentioning
confidence: 99%